2017
DOI: 10.1177/1749975517722476
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Marriage Rates Despite High Individualization: Understanding the Role of Internal Reference in Swedish Marriage Discourse

Abstract: Individualization remains the most prominent theoretical explanation for the shifts in European demographic trends since the 1960s, including decreasing marriage and fertility rates and increasing divorce rates. Demographic theorists suggest that a shift from traditional to individualized values, such as autonomy and self-realization, has been driving these trends. However, conceptualizing individualization as a set of values cannot account for why Swedish marriage rates have increased since 1998, despite high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…We use an experimental method drawn from cognitive psychology to make spheres relevant to the hostile worlds cultural belief, close relations and money, salient. Our results provide evidence of how a widely shared cultural belief can affect cognition related to childbearing at the individual level (see Strandell 2018 for a similar argument about cognition related to marriage using qualitative methods). Participants who are first exposed to the sphere of close relations are less likely to report that monetary concerns are relevant to their decisions about having children.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We use an experimental method drawn from cognitive psychology to make spheres relevant to the hostile worlds cultural belief, close relations and money, salient. Our results provide evidence of how a widely shared cultural belief can affect cognition related to childbearing at the individual level (see Strandell 2018 for a similar argument about cognition related to marriage using qualitative methods). Participants who are first exposed to the sphere of close relations are less likely to report that monetary concerns are relevant to their decisions about having children.…”
Section: Discussionsupporting
confidence: 57%
“…We apply the implicit activation mechanism to the domain of childbearing in order to better understand how culture and cognition shape associations with childbearing and related behaviors. The agenda for this type of work has been developed in theoretical contributions by demographers (e.g., Bachrach 2014; Bachrach & Morgan 2013; Thornton et al 2012; Johnson-Hanks et al 2011) as well as in recent empirical studies (e.g., Frye 2017; Marshall & Shepherd 2018; Rackin & Bachrach 2016; Strandell 2018). This emerging literature underscores that fertility decisions are the product not only of rational calculation and deliberate cognition, but also of supraindividual cultural factors—widely shared beliefs and assumptions.…”
Section: Implicit Activation Mechanism and The Interaction Of Culturamentioning
confidence: 99%
“…Marriage here is likely to indicate union stability and, to some extent, stronger familial values. It is not certain that marriage in the Nordic countries represents traditional values (see Duvander 1999;Strandell 2017;Ohlsson-Wijk, Brandén, and Duvander 2018), but it represents a serious intention to stay together. Thus, the selection into marriage probably influences continued childbearing.…”
Section: Methodsmentioning
confidence: 99%
“…Given that Sweden is continuously ranked as an extreme country on measures of individualized values such as secularism and self-expression (World Values Survey, 2015), this upward trend for marriage may seem contradictory. However, it has been suggested that the Swedish institution of marriage has become so dissociated from tradition, religion, and stereotyped gender roles that it is no longer considered to be in conflict with individualized values such as autonomy or self-realization (Strandell, 2018). Rather, it is viewed as a personal choice that people make based on legal-practical reasons, or as a symbolic declaration of commitment and belonging (Strandell, 2018).…”
Section: Romantic Relationships In the Swedish Contextmentioning
confidence: 99%
“…However, it has been suggested that the Swedish institution of marriage has become so dissociated from tradition, religion, and stereotyped gender roles that it is no longer considered to be in conflict with individualized values such as autonomy or self-realization (Strandell, 2018). Rather, it is viewed as a personal choice that people make based on legal-practical reasons, or as a symbolic declaration of commitment and belonging (Strandell, 2018). Taken together, it seems that being involved in a committed romantic relationship is normative among young adults in Sweden, with cohabitation and marriage being two equally accepted forms of union.…”
Section: Romantic Relationships In the Swedish Contextmentioning
confidence: 99%